The Effects of Task-based Language Teaching and Audio-lingual Teaching Approach in Mandarin Learning Motivation - Wen, Chua Hui; Ying, Lin Chia; Huat, Ang Thiah; Azlan, Mohammad Affiq Bin Kamarul; Shy, Fan Pik; Baoshun, Shan (Universitas Negeri Makassar, 2021)
This study investigates the effects of Task-based Language Teaching (TBLT) and the Audio-Lingual Teaching Approach (ALTA) on learning motivation among non-native Mandarin learners in the Teaching of Mandarin as a Third Language (TMTL). The TBLT applied is an adaptation of Willis's TBL Framework, while the ALTA applied is an adaptation of SarÄ±Ã§oban's dialogue memorisation. A quasi-experimental design was used in this study, with 21 students selected through convenience sampling for TBLT and 22 students for ALTA. Motivational Strategies for Learning Questionnaire (MSLQ) was employed. A descriptive analysis was conducted to compare if any changes in learning motivation and learning anxiety components for both groups before and after TBLT and ALTA were adopted in the learning interventions. The descriptive analysis showed that there were changes in the aspect of learning motivation and learning anxiety component. The result indicated that there was an increment in the number of students of the group with a very high level of learning motivation for TBLT. The result ranged from 8 students (38%) to 11 students (52%); the ALTA group remained unchanged as 11 students (50%) had a high level of learning motivation, and 11 students (50%) had a very high level of motivation. As for the learning anxiety component, the TBLT group showed a decrease in the number of students having very high anxiety, from 2 students (10%) dropped to 0 student (0%). Meanwhile, for the ALTA group, the results indicated that anxiety level for students had increased; the number of students who experienced a very high level of anxiety had increased from 2 students (9%) to 6 students (27%). The study indicates that TBLT has a positive effect on Mandarin learning motivation, which TBLT might help in reducing students' learning anxiety. Still, ALTA might, on the other hand, increase learning anxiety. The study implies that TBLT might be a better approach to learning Mandarin and might promote better performance among non-native speakers.